Procedural Volume and Outcomes After Percutaneous Coronary Intervention for Unprotected Left Main Coronary Artery Disease—Report From the National Clinical Data (J‐PCI Registry) - Tadao Aikawa; Kyohei Yamaji; Toshiyuki Nagai; Shun Kohsaka; Kiwamu Kamiya; Kazunori Omote; Taku Inohara; Yohei Numasawa; Kenichi Tsujita; Tetsuya Amano; Yuji Ikari; Toshihisa Anzai (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background There is a limited evidence base to support the volume‐outcome relationship in patients undergoing percutaneous coronary intervention (PCI) for unprotected left main coronary artery disease (UPLMD). This study aimed to evaluate the relationship between institutional and operator volume and in‐hospital outcomes in patients undergoing PCI for unprotected left main coronary artery disease. Methods and Results We analyzed characteristics and clinical outcomes of 24 320 patients undergoing PCI for unprotected left main coronary artery disease at 1102 hospitals by 7244 operators using data from the Japanese nationwide J‐PCI Registry (National PCI Data Registry) between January 2014 and December 2017. We classified institutions and operators into quartiles based on the mean annual volume of PCI. A generalized linear mixed‐effects model was used to evaluate the association between institutional and operator PCI volume and in‐hospital outcomes. Among the 24 320 patients, 4027 (16.6%), 6147 (25.3%), and 14 146 (58.2%) presented with ST‐segment–elevation myocardial infarction, non–ST‐segment–elevation acute coronary syndrome, and stable ischemic heart disease; their crude in‐hospital mortality was 15%, 3.1%, and 0.3%, respectively. Compared with patients in the lowest quartile of institutional volume (1–216 PCIs/y), the adjusted odds ratio of in‐hospital death in patients in the second (217–323 PCIs/y), third (324–487 PCIs/y), and fourth (488–3015 PCIs/y) quartile of institutional volume was 0.75 (95% CI, 0.51–1.10; P=0.14), 0.87 (95% CI, 0.57–1.34; P=0.54), and 0.51 (95% CI, 0.30–0.86; P=0.01), respectively. These findings were consistent in rates of in‐hospital death or any complication. Conversely, operator PCI volume was not significantly associated with in‐hospital outcomes. Conclusions Institutional rather than operator‐based PCI volume was associated with better in‐hospital outcomes in patients undergoing PCI for unprotected left main coronary artery disease.